Differential post-transcriptional activation of human phagocytes by different Pseudomonas aeruginosa isolates. - Pollard, A; Currie, A; Rosenberger, C; Heale, J; Finlay, B; Speert, D (2004)
Pseudomonas aeruginosa is a pulmonary pathogen in individuals with impaired mucociliary clearance such as cystic fibrosis or mechanical ventilation. Non-opsonic phagocytosis of P. aeruginosa can be mediated by either CR3 or CD14 and different strains appear to have a bias towards one or the other receptor. Strain Fc808 is ingested through CD14 whereas P1 (Fc194) uses CR3. In an in vitro culture system, the inflammatory response of macrophages to these two different strains of P. aeruginosa was divergent at the protein level, with higher IL-6 and tumour necrosis factor (TNF)-alpha production generated in response to strain P1 and higher IL-1 beta production in response to strain Fc808. Interaction of macrophages with these two bacterial strains induced distinct gene expression patterns as detected by gene array analysis, with prominence of genes encoding pro-inflammatory cytokines, surface receptors, transcription factors and proteins involved in phagocytosis. However, comparison of gene expression data and cytokine response data with the two bacterial strains indicated that production of IL-1 beta, IL-6 and TNF-alpha was under differential post-transcriptional control. Interestingly, this effect did not correlate with receptor bias but instead was related to the different LPSs of the two strains. The use of specific mitogen-activated protein kinase (MAPK) inhibitors suggested a role for extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) in the differential cytokine production by strains P1 and Fc808. These results indicate that strains of the same species of bacteria may induce differential macrophage phagocytic and inflammatory responses with likely consequence for bacterial clearance and host injury.